Factors affecting 30-day postoperative complications after emergency surgery during the COVID-19 outbreak: A multicentre cohort study. (September 2021) - de Bock, Ellen; Filipe, Mando D.; Pronk, Apollo; Boerma, Djamila; Heikens, Joost T.; Verheijen, Paul M.; Vriens, Menno R.; Richir, Milan C.
Abstract: Introduction: Coronavirus disease 2019 (COVID-19) has influenced (surgical) care worldwide. Measures were taken to prioritize surgical care in order to maintain capacity for COVID-19 healthcare. However, the influence of these measures on emergency surgery is limited. Therefore, the aim of this study is to describe the trends in emergency surgery and determine the factors influencing the risk of postoperative complications during the first wave of the COVID-19 pandemic. Methods: This multicentre retrospective cohort study investigated all emergency patients operated on from March 9th to June 30th, 2020. The primary endpoint was identifying the number of emergency surgical procedures performed. Secondary endpoints were determining the number of postoperative complications and factors determining the risk of postoperative complications, which were calculated by multivariate analysis with odds ratio (OR) and 95% confidence (CI) intervals. Results: In total, 1399 patients who underwent an emergency surgical procedure were included. An increase in the number of emergency vascular and trauma surgical procedures occurred during the study period. In contrast, the number of emergency general and oncological surgical procedures performed remained stable. An increased age (OR 1.01, 95% CI 1.00–1.02; p = 0.024), American Society of Anaesthesiologists (ASA) (OR 1.34, 95% CI 1.09–1.64; p = 0.005), and surgical discipline were independent predictors for an increased risk of postoperative complications. Conclusion: The performance of emergency vascular and trauma surgical procedures increased. The performance of emergency general and oncological surgical procedures remained stable. In addition, increased age, ASA, and surgical discipline were independent predictors for an increased risk of postoperative complications. Highlights: An increased number of emergency vascular and trauma surgical procedures occurred. The number of emergency oncological and general surgical procedures remained stable. Age, ASA, and surgical discipline were factors for increased risk of complications. No increase in the number of postoperative complications was observed.